Women and the politics of place: ruminations and responses - Graham Julie (2002)
Julie Graham connects the categories used by the introductory paper to the project - `place', `women' and `politics' - to the economic politics that she and Katherine Gibson are engaged in with several communities in the US, Australia and the Asia Pacific region. This political work builds upon the specificity of places with existing economic identities, resources and capacities; it draws on the willingness and ability of women to become subjects of non-capitalist development; and it pursues a politics of language in constructing diverse community economies in the face of globalization. - Reproduced.
Keywords: Women